Patterns and universals of adult romantic attachment across 62 cultural regions: are models of self and of other pancultural constructs? - Schmitt, David P. (2004)
As part of the International Sexuality Description Project, a total of 17,804 participants from 62 cultural regions completed the Relationship Questionnaire (RQ), a self-report measure of adult romantic attachment. Correlational analyses within each culture suggested that the Model of Self and the Model of Other scales of the RQ were psychometrically valid within most cultures. Contrary to expectations, the Model of Self and Model of Other dimensions of the RQ did not underlie the four-category model of attachment in the same way across all cultures. Analyses of specific attachment styles revealed that secure romantic attachment was normative in 79% of cultures and that preoccupied romantic attachment was particularly prevalent in East Asian cultures. Finally, the romantic attachment profiles of individual nations were correlated with sociocultural indicators in ways that supported evolutionary theories of romantic attachment and basic human mating strategies.